Reproducibility of the Patient Setup for Head and Neck Cancers using On-Board Imager System - Masa-Nga, Wilai; Thonapan, Natchayaporn; Suntiwong, Sawanee; Dachaworakol, Kittipol; Thongsawat, Sangutid; Khamfongkhruea, Chirasak; Pattaranutraporn, Pittayapoom; Tannanonta, Chirapha (The ASEAN Journal of Radiology, 2023)
Objective: To study the setup error of patient positioning in head and neck cancer with customized thermoplastic long mask using On-Board Imager (OBI) system. Materials and Methods: This study is a retrospective analysis of the setup error data from June 2008 to February 2009. The data were collected from 12 head and neck cancer patients with IMRT technique using the thermoplastic long mask for 6 MV photon beams. Two images in AP (anteriorposterior) and lateral views were taken with the On-Board Imager mounted on the gantry of the linear accelerator machine before treating the patient. Then these images were matched with the DRR (Digital Radiographic Reconstruction) images of planning CT by using the OBI software to determine the setup errors in vertical (anterior-posterior), longitudinal (superior-inferior), and lateral (left-right) directions. Results: From 187 sessions of the matching, the mean values of setup error were 0.19 ± 0.18 cm. 0.21 ± 0.18 cm, and 0.11 ± 0.11 cm for vertical (Vrt), longitudinal (Lng), and lateral (Lat) directions respectively. The maximum setup errors were 0.9 cm. 0.6 cm. and 0.5 cm for Vrt. Lng. and Lat directions from two patients with cutting thermoplastic long mask at the port and neck regions. For normal masks, the maximum values were 0.5 cm, 0.5 cm, and -0.5 cm for Vrt. Lng, and Lat directions. Conclusion: All setup errors in head and neck cancer of this study are acceptable for thermoplastic long mask without cutting. The OBI system is shown to be useful for reducing the uncertainty of interfraction and increasing the efficiency of radiation therapy.